Analysis of Arabic Teaching Materials on Marhaban Academy's TikTok Account - Aufa, Adila Umniati; Ahkas, Akmal Walad (Universitas Yudharta Pasuruan, 2024)
Social media especially TikTok, offers significant potential as an effective and engaging learning tool. Marhaban Academy is a prime example of harnessing this platform to deliver innovative Arabic language teaching materials. This study aims to conduct a thorough analysis of the Arabic language learning content presented by Marhaban Academy on TikTok using a qualitative approach and Miles and Huberman's data analysis model. Through data reduction, data presentation, and conclusion drawing stages. The study findings indicate well-presented teaching materials with relevant content and the use of multimedia such as animation, colored text, and visuals to enhance user engagement. However, there is a need for systematic improvement in the coherence of Arabic language concepts and more structured evaluation strategies to enhance learning effectiveness. This study provides insights into the potential and challenges of Arabic language education through the TikTok platform as implemented by Marhaban Academy.